Coursework grades feedback and moderation system for The Marker’s Apprentice (TMA) - Madu, Nnanna Emmanuel (2014)
Recent studies have identified low quality feedback as the primary reason why many students fail to use the feedback provided to them. Currently, there is no known system solely dedicated to the delivery of high-quality coursework feedback to students. This project bridges this gap through the development of a coursework grades feedback and moderation system. The system operates on student results from The Marker’s Apprentice (TMA), a marking application developed at the University of Nottingham. Web engineering, a methodology which applies a systematic approach to the implementation of web-based systems, has been adopted in the development of the system. The system allows students view their coursework feedback according to the marking scheme. It also allows moderators check coursework grades for possible marking inconsistencies. This work includes a cooperative evaluation which examines how users perceive the functionality and usability of the system. The evaluation results were generally positive, with over two-thirds of respondents satisfied with the suitability of the system for viewing coursework feedback and performing grades moderation.